Role of plasma instabilities driven by oxygen ions during magnetic storms and substorms - Lakhina, G.S.; Singh, S.V. (My University, 2003)
Ionospheric-origin O+ ions constitute an important and some times dominant part of the ring current and the near-Earth plasma sheet region during geomagnetic storms and substorms. Low-frequency instabilities excited by the energetic oxygen ions in the near-Earth plasma sheet and ring current region during the geomagnetic storms/substorms are investigated. It is shown that the presence of ionospheric-origin oxygen ion beams with anisotropic pressure can excite helicon mode instability in the near-Earth plasma sheet region provided their Alfvenic Mach numbers lie in a certain range. The helicon modes are easily excited under the conditions when the usual long wavelengths fire-hose modes are stable. On the other hand, low-frequency quasi-electrostatic loss-cone type instabilities can be driven by the energetic oxygen ions in the storm time ring current region. These instabilities may scatter ring current particles and contribute to the ring current decay.
Keywords: Magnetosphere; Magnetic storms; Magnetospheric substorms; Ionosphere; Space environment; Oxygen ions; Plasma instabilities